Synophtalmia on a Newborn - Bira, Laetitia Bihamba; Sikakulya, Franck Katembo; Mumbere, Mupenzi; Mathe, Jeff (SAGE Open Medical Case Reports, 2022)
Synophtalmia or cyclopia is a rare presentation of alobar holoprosencephaly. Cases which have been reported are stillborn or dead in post-delivery period. We are presenting a 3000-g live full-term newborn girl delivered by caesarean section with a well-marked cyclopia, but who died 30min post-delivery. The case did not present with other abnormalities. The literature showed that genetic disorders are associated with cyclopia. A prenatal anomaly scan can help in the early detection of the condition and timely termination of the pregnancy can be conducted.
Keywords: Cyclopia; Newborn; Synophtalmia